2020
DOI: 10.3390/su12145808
|View full text |Cite
|
Sign up to set email alerts
|

Karren Habitat as the Key in Influencing Plant Distribution and Species Diversity in Shilin Geopark, Southwest China

Abstract: Karst rocky desertification (KRD) is one of the biggest challenges in the karst ecological restoration of Southwest China, and a thorough understanding of the plant community characteristics in various karren habitats provides a basis for mitigating KRD and restoring the degraded ecosystem. To improve our knowledge of the detailed characteristics and impact mechanisms of karren habitats on the species distribution and species diversity patterns of woody and herbaceous plants to benefit sustainable management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Dalam hal penilaian harga jasa ekonomi sebagai bagian dari tujuan ekowisata dan fungsi ekologi, data diversitas flora sangat dibutuhkan [16]. Lebih lanjut data keragaman flora menjadi sumber rujukan dalam pengelolaan vegetasi secara berkelanjutan, maupun dalam upaya restorasi jika terjadi kerusakan [17].…”
Section: Cyathea Orientalisunclassified
“…Dalam hal penilaian harga jasa ekonomi sebagai bagian dari tujuan ekowisata dan fungsi ekologi, data diversitas flora sangat dibutuhkan [16]. Lebih lanjut data keragaman flora menjadi sumber rujukan dalam pengelolaan vegetasi secara berkelanjutan, maupun dalam upaya restorasi jika terjadi kerusakan [17].…”
Section: Cyathea Orientalisunclassified
“…Furthermore, little association between degraded karst tiankeng and species composition has been made in independent studies of species diversity (Jian et al, 2018;Zhang et al, 2019). Relevant studies on environmentplant relationships have shown that cryptic habitats in karst landscapes have high species diversity, and new taxa have been identified (Parmentier and Hardy, 2009;Li et al, 2020;Peng et al, 2020;Liu et al, 2021;Ren et al, 2021). However, little is known about how the flora composition and diversity varies and what effects that degraded karst tiankengs inserted in a karst forest matrix may exert on these plant communities.…”
Section: Introductionmentioning
confidence: 99%
“…Karst landscapes easily degraded into karst rocky desertification (KRD) landscapes because of intensive unreasonable human activities and the vulnerable carbonate environment in southwestern China (Li et al 2020a(Li et al , 2020b. In recent decades, Chinese governments have initiated several ecological restoration projects, including the Natural Protection Project and the Karst Rocky Desertification Restoration Project (Tong et al 2018;Wang et al 2019), which aim not only to restore the ecological function, but also to restore its aesthetic values (Li et al 2020a(Li et al , 2020b. Tong et al (2018) presented the remarkable ecological benefits of restoration projects in karst area, yet visual aesthetic consequences of the restored landscape, surprisingly, have received less attention (Dou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This unique geomorphological environment features contiguous distribution of bare and shallow carbonate rock, which determines the high fragility of the karst ecosystem, especially in the context of climate change (Yang et al 2011;Xu et al 2013). Karst landscapes easily degraded into karst rocky desertification (KRD) landscapes because of intensive unreasonable human activities and the vulnerable carbonate environment in southwestern China (Li et al 2020a(Li et al , 2020b. In recent decades, Chinese governments have initiated several ecological restoration projects, including the Natural Protection Project and the Karst Rocky Desertification Restoration Project (Tong et al 2018;Wang et al 2019), which aim not only to restore the ecological function, but also to restore its aesthetic values (Li et al 2020a(Li et al , 2020b.…”
Section: Introductionmentioning
confidence: 99%